2010
DOI: 10.1299/jmmp.4.1273
|View full text |Cite
|
Sign up to set email alerts
|

Strength of VGCF/Al Composites for High Thermal Conductivity

Abstract: In this paper, the evaluation of the strength of the VGCF/Aluminum composites which have high thermal conductivity is reported. VGCF (Vapor Growth Carbon Fiber) is a kind of the Carbon nanotube (CNT) which has very high thermal conductivity as well as CNT. The composites are made by spark plasma sintering. The stress-strain curves of the composites are obtained by the tensile tests and show that the composites have brittle behavior. The brittleness of the composites increases with increase in the volume fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Figure 7 shows examples of the stress-strain relations of the composites. Figure 7(a) showed stress-strain relations still fracture [22]. Figure 7(b) shows stress-strain relation and the circles and squares show the stress-strain relations of the matrix and the composite containing 30% of VGCF, respectively.…”
Section: Experimental Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 7 shows examples of the stress-strain relations of the composites. Figure 7(a) showed stress-strain relations still fracture [22]. Figure 7(b) shows stress-strain relation and the circles and squares show the stress-strain relations of the matrix and the composite containing 30% of VGCF, respectively.…”
Section: Experimental Methodsmentioning
confidence: 97%
“…6 Geometry of test specimens. (mm) (a)still fracture [22] (b)prestrain Fig. 7 Example of stress-strain relations of the composites.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the composites had high thermal conductivities and further suggested that the high thermal conductivities arise from VGCF-CNT networks in the composite (5,6). In this paper, temperature dependences of both thermal conductivities and strength properties of the composite are investigated.…”
Section: Introductionmentioning
confidence: 95%
“…There are only a few reports considering the improvement of the thermal conductivity. The authors have fabricated Al matrix composites containing CNT and VGCF using SPS, and showed that the composites had high thermal conductivities and further suggested that the high thermal conductivities arise from VGCF-CNT networks in the composite (Imanishi et al, 2008(Imanishi et al, , 2009Fukuchi et al, 2010). The maximum volume fraction of VGCF of the composites was 60% to obtain the high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%